2023
DOI: 10.3390/diagnostics13061020
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Immunohistochemistry in the Evaluation of Tumor Depth of Primary Cutaneous Melanoma

Abstract: Primary cutaneous melanoma (PCM) is the most aggressive skin malignancy, with an increasing incidence and significant mortality. Tumoral invasion, expressed as Breslow thickness, is routinely assessed on hematoxylin and eosin (HE), although this stain may sometimes underestimate the tumoral depth. The aim of this study was to compare the efficiency of the immunohistochemical (IHC) markers S-100, SOX10, Melan-A, and HMB-45 with HE for the evaluation of the Breslow thickness and staging of PCM. This retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In contrast, IHC is considered the most easily adopted test, as it overcomes the aforementioned restrictions and limitations [ 25 ]. While the rate of IHC utilization has significantly increased in recent years [ 26 , 27 , 28 ], properly validated and standardized markers for adoption in clinical melanoma practice remain an issue. In this study, more than 80% of the respondents currently requested IHC tests to confirm a melanoma diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, IHC is considered the most easily adopted test, as it overcomes the aforementioned restrictions and limitations [ 25 ]. While the rate of IHC utilization has significantly increased in recent years [ 26 , 27 , 28 ], properly validated and standardized markers for adoption in clinical melanoma practice remain an issue. In this study, more than 80% of the respondents currently requested IHC tests to confirm a melanoma diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…HMB-45 and Melan-A/MART-1 are melanocyte-specific markers with considerable specificity. HMB-45 recognizes gp100, a component of the melanosomal complex, and is highly specific for melanoma [65][66][67]. HMB-45 is particularly useful in distinguishing between a benign and a malignant melanocytic tumor as nevi gradually lose HMB-45 due to their maturation process [67,68].…”
Section: Diagnostic and Prognostic Immunohistochemical Markers In CMmentioning
confidence: 99%
“…Melan-A expression is predominantly localized within the endoplasmic reticulum and melanosomes, thus having higher sensitivity compared to HMB-45. Melan-A is particularly useful in identifying isolated tumoral melanocytes in the dermis, which can reclassify a melanoma initially diagnosed as in situ to an invasive lesion [66,71,72]. Drabeni M. et al reported an increased Breslow thickness in approximately 60% of cases when utilizing Melan-A compared to H&E staining alone [71].…”
Section: Diagnostic and Prognostic Immunohistochemical Markers In CMmentioning
confidence: 99%